2016
DOI: 10.4049/jimmunol.1501629
|View full text |Cite
|
Sign up to set email alerts
|

TLR-Activated Gap Junction Channels Protect Mice against Bacterial Infection through Extracellular UDP Release

Abstract: Extracellular UDP (eUDP), released as a danger signal by stressed or apoptotic cells, plays an important role in a series of physiological processes. Although the mechanism of eUDP release in apoptotic cells has been well defined, how the eUDP is released in innate immune responses remains unknown. In this study, we demonstrated that UDP was released in both Escherichia coli–infected mice and LPS- or Pam3CSK4-treated macrophages. Also, LPS-induced UDP release could be significantly blocked by selective TLR4 in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
34
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 34 publications
(37 citation statements)
references
References 36 publications
3
34
0
Order By: Relevance
“…Recently, Qin et al (20) found that Cx43 is the most abundant connexin in RAW 264.7 cells and that its expression is increased by LPS, consistent with our findings. Additionally, growing evidence has indicated that connexins are involved in inflammatory signaling, such as adhesion molecule expression and leukocyte transmigration (21,22).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Recently, Qin et al (20) found that Cx43 is the most abundant connexin in RAW 264.7 cells and that its expression is increased by LPS, consistent with our findings. Additionally, growing evidence has indicated that connexins are involved in inflammatory signaling, such as adhesion molecule expression and leukocyte transmigration (21,22).…”
Section: Discussionsupporting
confidence: 93%
“…In contrast, GSK650349 and Torin2 inhibited the upstream components of the mTOR/SGK/Cx43 signaling pathway, thereby suppressing the movement of a broad range of myeloid cells. Additionally, inhibition of macrophage recruitment by blocking the hemichannel may partly contribute to weakened bacteria clearance because Cx43-mediated UDP release may be involved in mediating the effects of Gap19 treatment (20). Furthermore, mice survival in the acute peritonitis mouse model was depressed by Gap19, which further confirmed the pivotal role of Cx43 hemichannel in the fight against bacterial infection.…”
Section: Discussionmentioning
confidence: 71%
“…Our data has shown that ATP released from peritoneal macrophages is an active process that occurs in response to TLR-2 and TLR-4 agonists in a CX43dependent manner. Increased expression of CX43 on macrophages following TLR-4 pathway activation has been previously shown (22). Our study has extended this observation by showing the functional role of CX43 for autocrine signaling in macrophages.…”
Section: Discussionsupporting
confidence: 84%
“…***p , 0.001. eliminate the potential damage from pathogens. Previous studies have shown that nucleotides, such as ATP, UTP, and UDP, could be released through multiple plasma membrane channels during different stages of infection (8,21). Moreover, the spatial and temporal release pattern of endogenous danger signals suggests different roles in the fight against invading pathogens.…”
Section: Discussionmentioning
confidence: 99%